Assessment of the livelihood status of the fish farmers in some selected areas of Bagmara upazilla under Rajshahi district - Ali, MH; Hossain, MD; Hasan, ANGM; Bashar, MA (Journal of the Bangladesh Agricultural University, 2010)
The present investigation was carried out to assess the livelihood status of the fish farmers in Hamirkutsha and Kamarbari Unions of Bagmara upazilla under Rajshahi district during June to December 2006. Data were collected through the use of well structured questionnaire. Fifty farmers were included in this study who were directly involved in fish farming. Average pond size was 0.13 ha with single (64%) and multiple ownerships (36%). Most of the fishers were belonged to the age category of 31 to 40 years and average education level of 9.86 years of schooling, represented by 94% Muslims and 6% Hindus. About 54% of the farmers have tinshed house while 26, 14 and 6% of the farmers have half-building, building and kacha house, respectively. Average annual incomes of majority of fish farmers were above Tk. 75,000 per annum and 62% of the farmers used semi-pucca sanitary, 28% used pucca sanitary while only 10% used katcha sanitary. About 62% of the farmers had electricity facilities while 38% did not have and 88% of the farmers used own tube-well, while 12% of the farmers used neighbor's tube-well. Forty six percent of the farmers received health service from village doctor or kobiraj, 18% have access to upazila health complex, 14% went to district hospital, 20% consulted with MBBS doctor and 2% of the farmers do not take any treatment due to lack of money. Lack of scientific knowledge, multiple ownerships and lack of capital for fish culture were the major constraints. Keywords: Constraints; Fish farmers; Health service; Livelihood status DOI: 10.3329/jbau.v6i2.4836 J. Bangladesh Agril. Univ. 6(2): 367-374, 2008